(untitled) (Revista Electrónica REDINE, 2018)
The purpose of present research was to sensitize the P-Coach in the axiological formation on the latinoamerican table tennis players of the under 11 category; through the participation of those who assume a double role as relatives and coaches in the formative process of table tennis. For this, a qualitative research was carried out, under the sociocritical paradigm and IAP methodology. The study was based on an eclectic approach, base on theories of Albert Bandura´s vicarious learning, the moral development of Lawrence Kholberg, the learning of table tennis of Glenn Tepper, the performance patterns of Phillipe Molodzoff, the Olympic Chart and the sport values of Gutierrez. The transformative action plan where the use of TICs was indispensable to ensure compliance with participation of 25 countries affiliated to the ULTM and more than 15 coaches. The AtlasTi software and the triangulation technique were used for the analysis of the qualitative data. The collected reflections evidence an awakening in the conscience on the importance that assumes a P-Coach in the formation on the table tennis players beyond the competition. An integral sport education base on values and assertive relationships in the long term.